Association of serum KLF5 and actinin-4 levels with prognosis of TACE treatment for hepatocellular carcinoma - LI Shunle, LI Rong, TIAN Yaya, RAN Xiaoli, ZHAO Yanpei, XU Meng (Jichu yixue yu linchuang, 2024)
Objective To explore the relationship between serum Krüppel-like factor 5(KLF5) and actinin-4 with prognosis of hepatocellular carcinoma (HCC) treated with transcatheter arterial chemoembolization (TACE). Methods From March 2015 to March 2020, 130 HCC patients admitted into the Second Affiliated Hospital were collected as study subjects and divided into HCC group and 86 patients with liver cirrhosis were collected as control group. After 3 years of postoperative follow-up, HCC patients were sub-divided into survival group (n=38) and mortality group (n=92) based on their survival outcomes. ELISA was applied to detect the level of serum KLF5 and actinin-4 in each group and analyzed the correlation between serum KLF5 and actinin-4 levels. Cox regression was applied to analyze the risk factors affecting the prognostic mortality of HCC patients; Receiver operating characteristic curve(ROC) was plotted to evaluate the predictive value of serum KLF5 and actinin-4 levels for the prognostic mortality of HCC patients. Results The serum level of KLF5 and actinin-4 in the mortality group was significantly higher than those in the survival group(P＜0.05); There was a positive correlation between serum level of KLF5 and actinin-4 in HCC patients(P＜0.001); Low differentiation, staging (CNLC) stage IIIa of China liver cancer staging (CNLC), vascular invasion and elevated level of KLF5 and actinin-4 were risk factors for prognostic mortality in HCC patients(P＜0.05); The area under the curve (AUC) of serum KLF5 and actinin-4 alone and in combination for predicting mortality in HCC patients was 0.835, 0.866, and 0.936, respectively, showing a high level of combined predicting function (Zcombination-KLF5=2.792, P=0.005, Zcombination-actinin-4=2.014, P=0.044). Conclusions Serum level of KLF5 and actinin-4 l found in HCC patients has a high predictive value for prognosis.